Changes in the financing of domestic research and development - Török, László (International Journal of Engineering and Management Sciences, 2019)
Nowadays, the fourth industrial revolution is taking place at an incredible speed, with innovation at its heart. Of this, R & D funding is of paramount importance, which is directly or indirectly one of the most important tools for increasing corporate competitiveness. The study examines trends in domestic R & D expenditures over the past one and a half decades. It focuses on the extent to which the financial crisis has affected the amount of funding resources and their structure. From an international comparison, Hungary and the European Union spend much less on research and development than those in the global competition. The impact of the crisis is reflected in the decline in the growth dynamics of R & D expenditures, but it has not been solved solely as a result of the crisis. Changes in the domestic structure of expenditures in recent years are encouraging and are in sync with the change in attitude that is considered desirable in R & D funding. If we examine the domestic statistical data more thoroughly, we can no longer be very satisfied. However, from trends in data from recent years, it becomes apparent that neither Hungary nor the European Union will achieve the 1.8 and 3.0 per cent of GDP R & D spending by 2020.